Numerical Analysis of Laminar Natural Convection in Square Enclosure with and without Partitions and Study Effect of pPartition on the Flow Pattern and Heat Transfer - Lafta Ghashim Jassim, Sajida (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
The problem of steady, laminar, natural convective flow in an square enclosure with and without partitions is considered for Rayleigh number (103-106) and Prandtl number (0.7). Vertical walls were maintained isothermal at different temperatures while horizontal walls and the partitions were insulated. The length of partition was taken constant. The number of partitions were placed on horizontal surface in staggered arrangement from (1– 3) and ratio of partition thickness (H/L= 0.033, 0.083, 0.124). The problem is formulated in terms of the vorticity-stream function procedure. A numerical solution based on a program in Fortran 90 with the finite difference method is obtained. Representative results illustrating the effects of the thickness and number of partitions on the contour maps of the streamlines and temperature are reported and discussed. In addition, the local Nusselt number is evaluated. Results show that the values of stream function (the strength of flow) in enclosure increases with the increasing Rayleigh number. As the number of partitions and thickness of partition increases, the strength of flow decreases. Mean Nusselt number increases with increasing Rayleigh number at different number of partitions. The numerical results are compared with available numerical results and experimental data and a good agreement is obtained.